MULTIPLE INTELLIGENCE DAN PEMANFAATANNYA DALAM PEMBELAJARAN BAHASA ARAB: STUDI LITERATUR - Rosda Aisyatul ‘A’izzi; Andi Ilham Razaq; Aulan Nuriyah; M Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2026)
This study examines the utilization of Multiple Intelligence theory in Arabic language learning and its contribution to improving learning effectiveness. The background of this research is based on the diversity of students’ abilities and learning styles, which are often not accommodated through conventional learning approaches. This study aims to analyze how Multiple Intelligence is implemented in Arabic language learning, identify its forms of application in the teaching and learning process, and explain its contribution to students’ engagement and understanding. The research employed a literature review method by analyzing various scientific journals, books, and relevant academic references published between 2016–2026. The findings indicate that the application of Multiple Intelligence in Arabic learning can be carried out through various strategies such as educational games, discussions, storytelling, music, role play, visual media, and collaborative activities adapted to students’ dominant intelligences. This approach contributes positively to increasing students’ motivation, participation, self-confidence, and comprehension in learning Arabic. In addition, Multiple Intelligence-based learning creates a more humanistic, active, and meaningful classroom atmosphere because it appreciates students’ diverse potentials and abilities. The study implies that Arabic language teachers need to develop innovative and flexible learning strategies that accommodate students’ multiple intelligences in order to improve the quality and effectiveness of Arabic language learning in schools.